(untitled) (Perner’s Contacts, 2011)
The contribution deals with an issue of attestation rest of driver in road transport. At the beginning of the contribution states the reasons on which it is possible to use form. The contribution notes that the form is not used in regular daily and weekly rest. The next section of the contribution contains a guide of attestation of rest driver in both analogue and digital tachographs.